121k views
4 votes
5=P (-2, 4)43If P = (-2, 4),then find:Ry=1 (P)2y=11 2345 -4 -3 -2 -1 0-1([?], [])-2-3-4ាEnter

5=P (-2, 4)43If P = (-2, 4),then find:Ry=1 (P)2y=11 2345 -4 -3 -2 -1 0-1([?], [])-2-3-4ាEnter-example-1

1 Answer

7 votes

We need to find the reflection of point P across the line y = 1.

Reflection across the line y = k transforms the point (x,y) into (x, 2k - y).

Applying this rule to the point P(-2, 4) with the line y = 1 (k = 1), we get:

P(-2, 4) → (-2, 2x1 - 4) → P'(-2, -2)

User Maheshiv
by
5.3k points